The Free2B Multi-Media Bullying Prevention Experience: An Exemplar of Scientific Edutainment - Leff, Stephen S.; Waasdorp, Tracy Evian; Paskewich, Brooke S.; Bevans, Katherine B.; Winston, Flaura K. (Frontiers in Psychiatry, 2020)
Objective The objective of the current article is to highlight an example of a new paradigm, Scientific Edutainment. The manuscript describes how educational researchers and technologists worked together to develop a multi-media bullying prevention experience, called Free2B for middle school students paying particular attention to ensure that the programming was not only relevant to all students but also was appealing and responsive to the needs of urban youth. Bullying is the most common form of aggression experienced among school-aged youth, which impairs students’ learning and social-emotional functioning and has financial costs to society. Given that the prevalence of bullying is highest in middle school, finding brief and feasible methods for motivating and sustaining change at this age is critically important, especially in the case of urban, under-resourced schools. Method In response to this challenge, multidisciplinary bullying prevention researchers collaborated with international technologists to develop the Free2B multi-media bullying prevention experience through an iterative Community-Based Participatory Research (CBPR) approach. In addition, the research team conducted a series of pilot studies to iteratively develop and initially evaluate the multi-media program, helping to ensure relevance specifically for urban middle school youth. Results Results from the pilot studies indicated that the vast majority of middle school students found the Free2B multi-media bullying prevention experience to be enjoyable, relevant to their needs, and addressed important strategies to handle peer bullying and victimization. In addition, the brief prevention experience was associated with increases in problem-solving knowledge, prosocial attitudes about bullying, increased sympathy, and confidence in handling peer conflicts. Conclusion The current paper illustrates the use of a new paradigm, termed Scientific Edutainment, as a way to combine evidenced-based developmental science with the latest in entertainment technology to provide innovative, engaging, and technologically-sophisticated educational programming.